Annotated checklist of the coral reef fishes in the Capricorn Bunker-Group, Great Barrier Reef, Australia - Russell, Barry C. (Townsville, Qld Great Barrier Reef Marine Park Authority, 1983)
Special publication series (Great Barrier Reef Marine Park Authority (Australia) ; 1.
Keywords: Great Barrier Reef Marine Park (Qld.); Fishes--Queensland--Great Barrier Reef